Accelerated aging versus realistic aging in aerospace composite materials. II. Chemistry of thermal aging in a structural composite - Dao, B.; Hodgkin, J.; Krstina, J.; Mardel, J.; Tian, W. (Journal of applied polymer science, 2006)
Samples of an aerospace structural epoxy composite (8552/IM7) were subject to long‐term (≈ 1 year) thermal aging at temperatures of 70°, 120°, 170°, and 200°C (in air). The changes to the chemical and physicochemical structure of the composite were analyzed by a range of different techniques, including gravimetric analysis, Fourier transform infrared (FTIR), and dynamic mechanical analysis (DMA) to compare the effects of different severities of degradation treatment. The results highlighted the large differences in chemical effects between the surface and the interior of the composite with very minor changes in the latter even at quite high aging temperatures and long aging times. The oxidative changes at the surface, however, varied from highly selective molecular changes for particular chemical groups at the lower aging temperatures (70° and 120°C), to quite general and extensive oxidative degradation at the higher aging temperatures (170° and 200°C). The results indicated that the mechanical changes in an aged composite of this type will vary greatly with the material thickness and surface protection as well as the aging temperature the composite is exposed to. © 2006 Wiley Periodicals, Inc. J Appl Polym Sci 102: 3221–3232, 2006